Analysis of Students' Self Regulated Learning Using Augmented Reality Media on Solar System Material at Class VII SMP - Apit Fathurohman; Eka Supriasih; Ida Sriyanti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2022)
With the implementation of some limited face-to-face learning, the effects of the COVID-19 epidemic have now started to significantly fade from education. This forces instructors to be creative so that children can still learn independently. Students who get inadequate online instruction generally behave passively when receiving offline instruction. To deal with the issues of 21st-century learning, technological use, the selection of interesting learning models, and media that are in line with the characteristics of the material, especially abstract material, are still necessary. To prepare students for real life and improve learning, technological application and the growth of student learning independently are important. The purpose of this study was to examine how media augmented with augmented reality helped students learn independently. There are up to 27 students in the seventh grade at SMPN 3 Rantau Bayur in this qualitative descriptive study. A student learning independence questionnaire was designed to collect data, and it was triangulated using learning observation sheets and teacher interviews. The three stages of the data analysis technique, according to Miles Huberman (1992), are data reduction, data presentation, and summary. The percentage technique was used to examine the learning independence data collected. As according statistics from the learning independence questionnaire, the average percentage in the medium category is 61 percent.